If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + (2x + -5) = 9 Reorder the terms: 3 + (-5 + 2x) = 9 Remove parenthesis around (-5 + 2x) 3 + -5 + 2x = 9 Combine like terms: 3 + -5 = -2 -2 + 2x = 9 Solving -2 + 2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 9 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 9 + 2 2x = 9 + 2 Combine like terms: 9 + 2 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| 5*3.5= | | 6x^2+20x-30=0 | | (2/5x)+(6/5)=11 | | 2x+70-3x=(-5x+7)2 | | 4/5x-4-2x=3/5(x+4) | | x-3=8x-32 | | 2a-7/3=7 | | h+9=5 | | (3p^2-5p+3)+(8p^2-6p)= | | 90-9y+6y=180 | | -5d+3(d-4)=12-2d | | -5d+3(d-4)=12-d | | 2x-7-6x-12= | | (3/2x)-(7/6)=1 | | -45-9x=-10-2x | | -5d+3(d-4)=2(6-d) | | 6x-58=8 | | 12m=36+4m | | 6x-58+8=180 | | log(3)*(4-5x)=1 | | -t/16=-7/8 | | 4n=-32+2n | | (18-3x)(-2-x)(4x+24)=0 | | 16x-4+58+66=180 | | 16x-4+58=66 | | 3n-2=-3+4n | | 4n+2.8=9.6 | | 2x=8x-8 | | x-4-7=4 | | 2y/3-4=8 | | 2m+4/3=60+m | | -m/2+5=16 |